Tahlîl al-Akhthâ' al-Imlâiyyah fî Kitâbati Hurûf al-Hamzah li Thullâbi al-Mubtadiîn Wihdah al-Lughah al-Nâsyiîn (Wulan) Bima'had al-Nâsyiîn al-Islâmiy Jrujugan Larangan Pamekasan - Rizqiyadi, Mohammad (IAIN Madura, 2020)
This paper discusses the errors that occur in writing hamzah letters and the factors that influence the errors in writing hamzah. This study aims to find an Error Analysis in writing hamzah that occurs in elementary students at An-Nasyi'in Islamic boarding school. In this study, researchers used qualitative research methods. In collecting data, researchers used instruments of observation, interviews, and documentation. Analysis of the data used is the Error Analysis with three stages, namely, identification of errors, interpretation of errors, and correcting errors. The results showed that: First, errors in writing hamzah occur in six aspects, namely: writing hamzah at the beginning of a word, in the middle of a word, at the end of a word, writing hamzah over a letter, writing hamzah over nibrah, and in writing hamzah washal. The most common mistake is in writing hamzah at the beginning of a word; Second, the factors that influence the error in writing hamzah, namely: excessive generalization, lack of understanding the rules of writing hamzah, lacking in practicing the rules of writing hamzah.